2013
DOI: 10.1111/jvh.12188
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in toll‐like receptors and retinoic acid‐inducible gene I and outcome of hepatitis C virus infection: a candidate gene association study

Abstract: We evaluated the effects of genetic variation in toll-like receptors (TLR), retinoic acid-inducible gene I (RIG-I) and their signalling pathways on spontaneous hepatitis C virus (HCV) resolution. We screened 95 single-nucleotide polymorphisms (SNPs) in 22 genes. SNPs significantly associated with resolution in the discovery cohort were genotyped in a validation cohort. Multivariate logistic regression adjusted for sex, hepatitis B surface antigen, HIV infection and the interleukin-28B rs12979860 SNP was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The SNPs in the gene coding for MAVS appeared to be associated with systemic lupus erythematosus in the Chinese population, albeit only in patients with renal nephritis and arthritis, respectively [47]. Another study did not find an association between either of the SNPs in the genes coding for RIG-I and MAVS and outcome of hepatitis C virus infections [48]. Other variants with more deleterious effects on RIG-I [45] and MAVS [49] expression or function are rare, and therefore are unlikely to play a significant role in the outcome of RSV infection at the population level.…”
Section: Discussionmentioning
confidence: 96%
“…The SNPs in the gene coding for MAVS appeared to be associated with systemic lupus erythematosus in the Chinese population, albeit only in patients with renal nephritis and arthritis, respectively [47]. Another study did not find an association between either of the SNPs in the genes coding for RIG-I and MAVS and outcome of hepatitis C virus infections [48]. Other variants with more deleterious effects on RIG-I [45] and MAVS [49] expression or function are rare, and therefore are unlikely to play a significant role in the outcome of RSV infection at the population level.…”
Section: Discussionmentioning
confidence: 96%
“…So far, polymorphisms in RIG-I have been shown to be associated with resistance to type I diabetes [ 28 ], a decreased antibody level in response to rubella vaccination [ 29 ] and modification of the innate immune response of human dendritic cells [ 30 ]. Polymorphisms in Ibo, a molecule downstream of MAVS, were also identified to be involved in spontaneous hepatitis C virus (HCV) infection resolution in two independent cohorts [ 31 ]. Therefore, we initially thought that variants in the MAVS gene should result in dysfunction of the innate immune system, especially in the infectious diseases due to the gene’s crucial role in antiviral signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we first reported that the R65W and R218C SNPs exerted inhibitory effects on antiviral signalling in response to dsRNA. The R65W variant is located in the CARD domain of MAVS; therefore this variant may affect the interaction of MAVS and RIG-I through alterations in surface structure and hydrophobicity [ 31 ]. Mutation in the CARD domain also affects the significantly reduced interaction of MAVS with TRAF3, as shown by co-IP assays [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of nuclear factor (NF)-κB through Toll-like receptor binding is considered to be the central initiating event of host responses to invasion of microbial pathogens, including encapsulated bacteria ( Rahman and McFadden, 2011 , Clausen et al, 2013 ). Innate and adaptive immune responses are dependent on activation of the NF-κB pathway ( Janssen et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%